Natural gas hydrates in the Rio Grande Cone (Brazil): A new province in the western South Atlantic. (November 2015) - Miller, Dennis J.; Ketzer, João Marcelo; Viana, Adriano R.; Kowsmann, Renato O.; Freire, Antonio Fernando M.; Oreiro, Sergio G.; Augustin, Adolpho H.; Lourega, Rogerio V.; Rodrigues, Luiz F.; Heemann, Roberto; Preissler, Adriane G.; Machado, Claudia X.; et al.
Abstract: The Rio Grande Cone is a large-scale fanlike feature in the continental slope of the Pelotas Basin, Southern Brazil, where ubiquitous world-class bottom simulating reflectors (BSRs) are readily observed in seismic records. With the purpose of searching for natural gas hydrate deposits in the Cone area, four oceanographic cruises were carried out between May 2011 and July 2013, leading to the discovery of two pockmark fields, active faults and gas hydrates in shallow sediments. Multichannel seismic, multibeam echo sounder, side scan sonar and sub-bottom profiler records were used to map the shallow section and select sites for piston core sampling. Gas hydrates were recovered in several piston cores within muddy sediments collected inside pockmarks displaying high backscatter in the multibeam and side scan sonar data. We present two representative piston cores where numerous levels of gas hydrates occur, along with degassing features, authigenic carbonate and soupy sediments. Gas dissociated from gas hydrate samples is dominantly methane (>99.78%) with minor quantities of ethane. The chemical and isotopic compositions of the gas strongly suggest a biogenic origin for the analyzed samples. These new findings are regarded as strong enough evidence to consider the Rio Grande Cone as a new gas hydrate province. Highlights: Here we describe the first gas hydrate occurrence of the western South Atlantic. The gas hydrate province is hereafter named Rio Grande Cone Gas Hydrate Province. Two new pockmark fields are for the first time described in the western South Atlantic. Methane forming the gas hydrates in the Rio Grande Cone is biogenic in origin.